2009
DOI: 10.1094/pdis-93-1-0108c
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Detection of ‘Candidatus Liberibacter’ Species in Zebra Chip Disease-Infected Potato Plants in the United States

Abstract: Zebra chip (ZC), an emerging disease causing economic losses to the potato chip industry, has been reported since the early 1990s in Central America and Mexico and in Texas during 2000 (4). ZC was subsequently found in Nebraska, Colorado, New Mexico, Arizona, Nevada, California, and Kansas (3). Severe losses to potato crops were reported in the last few years in Mexico, Guatemala, and Texas (4). Foliar symptoms include purple top, shortened internodes, small leaves, enlargement of the stems, swollen axillary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 1 publication
1
36
0
1
Order By: Relevance
“…However, recent studies conducted in US, Mexico, and New Zealand have shown that zebra chip is associated with a previously undescribed species of the bacterium Candidatus Liberibacter vectored by the potato psyllid, Bactericera cockerelli Sulc (Munyaneza et al 2007a, b;Hansen et al 2008;Liefting et al 2008;Munyaneza et al 2008;Abad et al 2009;Crosslin and Bester 2009;Crosslin and Munyaneza 2009;Liefting et al 2009a, b;Lin et al 2009;Munyaneza et al 2009;Secor et al 2009). Effective monitoring and control of the potato psyllid are essential in order to better manage zebra chip in potatoes (Goolsby et al 2007;Gharalari et al 2009;Munyaneza, unpublished data).…”
mentioning
confidence: 99%
“…However, recent studies conducted in US, Mexico, and New Zealand have shown that zebra chip is associated with a previously undescribed species of the bacterium Candidatus Liberibacter vectored by the potato psyllid, Bactericera cockerelli Sulc (Munyaneza et al 2007a, b;Hansen et al 2008;Liefting et al 2008;Munyaneza et al 2008;Abad et al 2009;Crosslin and Bester 2009;Crosslin and Munyaneza 2009;Liefting et al 2009a, b;Lin et al 2009;Munyaneza et al 2009;Secor et al 2009). Effective monitoring and control of the potato psyllid are essential in order to better manage zebra chip in potatoes (Goolsby et al 2007;Gharalari et al 2009;Munyaneza, unpublished data).…”
mentioning
confidence: 99%
“…En Estados Unidos la enfermedad causada en la papa por Ca. L. solanacearum se le conoce como Zebra Chip (ZC) debido al pardeamiento que ocasiona en la pulpa del tubérculo (Abad et al, 2009;Liefting et al, 2009), e inicialmente a la bacteria se le nombro Candidatus Liberibacter psyllaurous (Hansen et al, 2008). Otro problema sanitario es el Amarillamiento del Psílido (AP), ocasionado según algunos autores por la inyección de toxinas que realiza el psílido Bactericera cockerelli Sulc.…”
Section: Introductionunclassified
“…The remainder of the 16S rRNA gene was sequenced and phylogenetic analysis showed that it is distinct from the three citrus-infecting liberibacter species described previously ). Subsequently, with the development of a specific PCR diagnostic method, this new liberibacter was also detected in potato (Solanum tuberosum), tamarillo (Solanum betaceum), cape gooseberry (Physalis peruviana) (Liefting et al, 2008a, b;Abad et al, 2009) and chilli (Capsicum sp.). A 1.7 kb fragment of the b operon containing the ribosomal proteins L10 (rplJ) and L12 (rplL) and the RNA polymerase beta subunit (rpoB) was amplified using the primer pair fp 1898/rp 1897 (Planet et al, 1995).…”
mentioning
confidence: 99%
“…We propose that the novel liberibacter species identified in solanaceous plants is named after its plant host family rather than the geographical region. Although this liberibacter species was first identified in New Zealand, it has subsequently been detected in potato plants exhibiting zebra chip symptoms in the USA (Abad et al, 2009). Zebra chip disease of potato was first reported in Mexico in 1994 and then in the USA in 2000 (Secor & Rivera-Varas, 2004).…”
mentioning
confidence: 99%